The effectiveness of using rebound exercises to develop the explosive power of arms and legs and forms of correction for Junior with a handball - Mubarak, Entidhar Jumaah; Neamah, Iqbal Abdulhussein; Hrebid , Nabeel Kadhim (International Journal of Psychosocial Rehabilitation, 2020)
The training in the sports field results depend on the integration in the physical, skill and planning preparation at the same time. This requires paying attention to all aspects, giving it the same importance and focusing on preparation, especially during the training process and mastering the skills. Through the experience of researchers being players and coaches, and during their observation of club training that some coaches tend to implement various methods and methods in developing strength in general and non-specialized through physical exercises for strength and perhaps some weight training and this is the reason for the insufficiency of the training process for the requirements of modern play, so he felt The researchers pointed to the use of regressive strength exercises in developing the explosive power of the arms and legs, and the forms of correction for Junior with a handball, to be an expressive way that the trainers would benefit in achieving good results. The research aims to: 1- Preparing the rebound force exercises to develop the explosive power of the arms and legs and the forms of correction for Junior with a handball. 2- Knowing the effect of using the rebound force exercises in developing the explosive power of the arms and legs and the forms of correction for Junior with a handball. The researchers used the experimental approach to suit the nature of the research problem. The research community identified the emerging players in the specialized center in the youth forum of Al-Qasim, who are (22) players. The most important conclusions were: 1-There is an evolution of the explosive power of the arms and legs and forms of aiming for emerging players with handball and for the control and experimental groups. 2- That the choice of the regressive strength exercises to develop the explosive power of the arms and legs was compatible with the working muscles of the skills of straightening shapes of the hand, which caused the effective impact in the development of its performance.